2021
DOI: 10.3390/jcm10235677
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Course of Plasma Trimethylamine N-Oxide (TMAO) Levels in ST-Elevation Myocardial Infarction

Abstract: The gut metabolite trimethylamine N-oxide (TMAO) at admission has a prognostic value in ST-elevation myocardial infarction (STEMI) patients. However, its sequential changes and relationship with long-term infarct-related outcomes after primary percutaneous coronary intervention (PCI) remain elusive. We delineated the temporal course of TMAO and its relationship with infarct size and left ventricular ejection fraction (LVEF) post-PCI, adjusting for the estimated glomerular filtration rate (eGFR). We measured TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…Interestingly, the post-MI rise in TMAO levels at each visit in our study was lower than the levels reported in previous study cohorts from the Netherlands, Japan, and China [ 17 19 ]. This finding is intriguing and raises the question whether this modest rise in TMAO is clinically significant for increasing the risk of future CVD events.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Interestingly, the post-MI rise in TMAO levels at each visit in our study was lower than the levels reported in previous study cohorts from the Netherlands, Japan, and China [ 17 19 ]. This finding is intriguing and raises the question whether this modest rise in TMAO is clinically significant for increasing the risk of future CVD events.…”
Section: Discussioncontrasting
confidence: 95%
“…Similarly, a decline in TMAO levels from admission (4.13 ± 4.37 μM) to 24 h (3.41 ± 5.84 μM), and an increase from 24 h to 4 months (3.70 ± 3.86 μM) in STEMI patients was reported by another recent study. Also, a decline in TMAO from admission to 4 months was inversely correlated (rho = − 0.16, p = 0.024) with infarct size [ 17 ]. The results of these studies underscore the clinical importance of repeated measurements of TMAO and its different fluctuation patterns during acute and chronic phases of post-ischemic events for predicting future CVD events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the research, gut microbiota may be an important diagnostic marker for CAD in the future (129). As an active metabolite synthesized by intestinal microbiota, the increased level of TMAO is associated with increased risks of CAD and all-cause mortality (130,131). In addition, Guo et al reported that associations of TMAO with CAD were sex-related (132).…”
Section: Tmao and Coronary Artery Diseasementioning
confidence: 99%
“…The pro-thrombotic activity of TMAO occurs due to the increase in calcium release from intracellular stores and enhancement of the platelet activation and responsiveness to different pro-coagulant factors, and consecutive thrombosis potential [ 134 ] via phosphorylation of ERK1/2/JNK in platelets [ 135 ]. In STEMI patients undergoing PCI, TMAO levels fluctuated during the 4-month follow-up and these changes predicted the infarct size, showing significant association, particularly in patients with impaired renal function, suggesting that TMAO could be involved in the ventricular remodeling [ 136 ].…”
Section: Gut Molecules and Cardiovascular Diseasesmentioning
confidence: 99%